Nilai-Nilai Pendidikan Sosial dalam Tradisi Bejango pada Masyarakat Sasak di Desa Bengkel Lombok Barat - Hidayattulloh Hidayattulloh; Suprapto Suprapto; Siti Nurul Yaqinah (Universitas Hamzanwadi, 2025)
One of the traditions that is often carried out by the residents of Bengkel Village until now is the Bejango tradition which is carried out after the marriage ceremony which has the aim not only to strengthen the ties of friendship between the families of the groom and bride but also to maintain and realize the values ​​of social education contained in the tradition. The purpose of this study was to find out how the Bejango tradition is carried out, the values ​​of social education contained in the Bejango tradition and efforts to maintain the existence of the Bejango tradition in Bengkel Village. This study uses a descriptive qualitative research method that analyzes the data findings with data obtained in the field. The data collection techniques used in this study were observation, interviews and documentation. The results of this study indicate that the Bejango tradition is a form of friendship between the bride's family and the groom. The process of the Bejango tradition consists of three stages, the first stage is the preparation stage, the implementation stage and the closing stage, in this Bejango tradition there are social education values, namely deliberation, mutual cooperation, hard work, unity and togetherness. There are also efforts to maintain the Bejango tradition, namely through socialization, providing education and involving village officials and community leaders.